A case of autoimmune pulmonary alveolar proteinosis with fluctuating lung shadows in parallel with cigarette smoke burden - Takahashi, Ayumu; Yamaguchi, Etsuro; Yonezawa, Toshiyuki; Kosaka, Kenshi; Matsubara, Ayako; Nishimura, Masaki; Tanaka, Hiroyuki; Yokoe, Norihito; Kubo, Akihito (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
The association between the development of pulmonary alveolar proteinosis (PAP) and dust inhalation has been established; however, the link between PAP and smoking is less clear. A 46-year-old man with mild bronchial asthma and a 52-pack-year smoking history was diagnosed with autoimmune PAP (APAP) based on computed tomography (CT) shadows, pathologic findings of the lung, and a high serum level of anti-granulocyte macrophage colony-stimulating factor (GM-CSF) IgG autoantibody. Smoking was stopped and he was treated three times with unilateral whole lung lavage (WLL). However, his respiratory failure did not improve because of incomplete WLL due to bronchospasm and decreased compliance of the ventilated lung during WLL. A fourth WLL was planned, but was cancelled because his respiratory status and lung shadows on CT scan unexpectedly improved immediately before WLL. During the follow-up period without smoking, the lung shadows resolved almost completely. However, the abnormalities relapsed after he resumed smoking and then modestly improved after changing to cigarettes containing less tar. Serum levels of anti-GM-CSF IgG were not compatible with the lung shadows. These observations in this patient suggested a link between smoking and APAP. Since variable smoking rates in patients with APAP have been reported in epidemiologic studies, a definite conclusion requires precise case-control studies in the future.